STRATEGIIKLANONLINE: STUDI IKLAN SHOPEE DIMEDIA SOSIAL (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
The business world in 2020 is said to be a golden year. There is no end to discussing business developments in the country. This is because Indonesia itself is a country that has extraordinary business development potential. Many analysts and observers say that Indonesia is a market that is too big to be a good habitat for business development which is followed by existing internet developments. Shopee is a buying and selling site or online market place that specifically provides buying and selling transactions. Advertisements often appear on internet or online social media. Likewise with the public, when they see Shopee advertisements in online media, many consumers are interested and carry out buying and selling transactions. They often buy products such as clothes, beauty tools and other accessory products. Shopee advertisements appear almost every time on social media, Shopee advertisements also offer discounts, free shipping, and quality goods.